Enhanced GABAergic Inhibition of Cholinergic Interneurons in the zQ175+/− Mouse Model of Huntington's Disease - Lim, Sean Austin O.; Surmeier, D. James (Frontiers in Systems Neuroscience, 2021)
Huntington’s disease (HD) is an autosomal dominant neurodegenerative disorder that initially manifests itself in the striatum. How intrastriatal circuitry is altered by the disease is poorly understood. To help fill this gap, the circuitry linking spiny projection neurons (SPNs) to cholinergic interneurons (ChIs) was examined using electrophysiological and optogenetic approaches in ex vivo brain slices from wildtype mice and zQ175+/- models of HD. These studies revealed a severalfold enhancement of GABAergic inhibition of ChIs mediated by collaterals of indirect pathway SPNs (iSPNs), but not direct pathway SPNs (dSPNs). This cell-specific alteration in synaptic transmission appeared in parallel with the emergence of motor symptoms in the zQ175+/- model. The adaptation had a presynaptic locus, as it was accompanied by a reduction in paired-pulse ratio but not in the postsynaptic response to GABA. The alterations in striatal GABAergic signaling disrupted spontaneous ChI activity, potentially contributing to the network dysfunction underlying the hyperkinetic phase of HD.